The effects of charismatic leadership on performance: exploring key boundary conditions at multilevel - Zhang, Linyuan; Seong, Jee Young; Hong, Doo-Seung; Yoon, Hye Jung (Frontiers in Psychology, 2025)
IntroductionCharismatic leadership (CL) plays an indispensable role in facilitating organizational change, stimulating creativity, and attaining performance objectives. Given the growing attention on the relationship between CL, creativity and performance, we establish a multilevel model that examines the moderated mediation effect of CL on task performance through creativity. This model considers both individual and group levels while accounting for contextual factors such as high-performance work systems (HPWS) at the individual level and group performance orientation (GPO) at the group level.MethodsOur analysis of field data gathered from members of work groups offers robust empirical support for our multilevel framework. Data were collected from team members and their leaders in Korean private-sector organizations, utilizing a final sample of 109 teams consisting of 1,080 members and 109 leaders for our analysis. Conducted ordinary least square (OLS) regression analysis were used to test the hypotheses.ResultsThe findings of this study indicate that CL exhibits higher creativity at the individual level when HPWS is low compared to high (compensatory effect). In contrast, CL produces higher group creativity at the group level when GPO is high rather than low (additive effect). Additionally, individual-level creativity mediates the relationship between the interaction of CL and HPWS at the individual level and task performance. The influence of the interactive effect of CL and GPO on performance at the group level is mediated by group-level creativity.ConclusionThis study emphasizes the significance of adopting a multilevel interactive perspective on creativity and performance while providing evidence for how leadership and its boundary conditions affect creativity and performance.